Output Reachable Set Analysis for Periodic Positive Systems - Ilyas Sitli (Hindawi Limited, 2021)
In this study, we use the union of the bounding hyperpyramids to estimate the output reachable set for periodic positive systems under two classes of exogenous disturbances. Optimization algorithms are used to obtain the smallest bounding hyperpyramids possible. Finally, numerical examples are given to verify the theoretical results.